Carboplatin plus paclitaxel weekly dose‐dense chemotherapy for high‐grade ovarian cancer: A re‐evaluation. (2nd November 2020) - Kessous, Roy; Matanes, Emad; Laskov, Ido; Wainstock, Tamar; Abitbol, Jeremie; Yasmeen, Amber; Salvador, Shannon; Lau, Susie; Gotlieb, Walter H.
Abstract: Introduction: We compared oncologic and clinical outcomes in patients with advanced ovarian cancer who received dose‐dense weekly paclitaxel with 3‐weekly carboplatin with those who received standard 3‐weekly chemotherapy. Material and methods: Comparison of all consecutive patients with advanced (International Federation of Gynecology and Obstetrics stages III‐IV) ovarian cancer who received a dose‐dense protocol between 2010 and 2016 with an immediate historical cohort of consecutive patients who received standard chemotherapy. Patients who received less than three cycles of treatment were excluded. Results: In all, 246 patients were included in the study, of whom 128 received the dose‐dense protocol and 118 were treated with the standard Q3‐week protocol. Patients in the dose‐dense group had significantly better progression‐free survival than those receiving the standard protocol (median progression‐free survival 22 vs 15 months; log rank = 0.026). The overall survival of patients in the dose‐dense group was also better than that of the patients in the standard protocol group; however, this difference was not statistically significant (median overall survival 66 vs 54 months; log rank = 0.185). The dose‐dense protocol remained significantly associated with favorable survival outcome in multivariable analysis adjusted for stage, histologic type, cytoreductive results and neoadjuvant chemotherapy. The use of the dose‐dense protocol was associated with higher rates of gastrointestinal, dermatologic, neurologic and hematologic side effects. Conclusion: Despite the limitations associated with the comparison to a historical cohort, a dose‐dense chemotherapy protocol resulted in a significantly improved progression‐free survival and the overall survival tended to be better, but this difference did not reach statistical significance compared with the standard chemotherapy protocol, and may be considered as a treatment alternative, albeit with some increased side effects.